Ultra-narrow Band Fano Resonance-Based All-Dielectric Optical Absorber Using Silica–Silicon Metamaterials - Ali Akbar Mashkour; Amangaldi Koochaki; Ali Abdolahzadeh Ziabari; Azadeh Sadat Naeimi (Electrica)
In this paper, an optical reflector is designed based on an all-dielectric metamaterial comprising silicon double bars with bent arms positioned on the surface of a silica layer. The proposed structure generates high-quality factor Fano resonance peaks within the visible spectrum, facilitated by the structural asymmetry introduced into the top layer of the metamaterial, i.e., the bar pairs. The use of dielectric materials instead of metal has resulted in lower plasmonic power loss and ultra-high quality factor peaks in the desired range. Simulation results show that the central wavelength, spectral width, and amplitude of the Fano resonance peaks can be adjusted by controlling the geometrical characteristics of the structure. Notably, an ultra-narrow Fano resonance peak of 0.26 nm at 682.78 nm wavelength has been achieved through the geometrical manipulation of the silicon bar pairs. Consequently, the proposed structure holds potential for applications in a variety of optical devices such as ultra-narrow band filters and high-resolution sensors.